Alterações em atributos químicos do solo pela aplicação de calcário na superfície ou incorporado - Freiria, Andre Costa [UNESP]; Mantovani, Jose Ricardo; Ferreira, Manoel Evaristo [UNESP]; Pessoa da Cruz, Mara Cristina [UNESP]; Yagi, Renato [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2008)
The application of lime oil the soil surface is necessary in son-le agricultural situations. The objective of this work was to verify changes ill chemical attributes of a medium texture soil as a result of lime application with and without amending. The experiment was carried out in a laboratory setting, in PVC columns, in a completely randomized design, with a 2 x 4 factorial design and a control, with four replicates, totaling 36 columns. The treatments were the combination of two little rates (4 and 2 t ha(-1)) and four types of little application (oil surface without amending, and amending in layers of 0 to 5; 0 to 10 and 0 to 20 cm depths), in addition to the control, to which lime was not applied. After 326 days of soil incubation with lime, there was a corrective effect front the lime until 5 cm or 10 cm below the depth in which there was the application or amending. The application of little resulted in increases of soil base saturation until 10 cm of depth, and until 40 cut of depth when the little was amended in the layers of 0 to 5, 0 to 10 or 0 to 20 cm depth.
Changes in soil chemical attributes from lime application on the surface or soil amending
Keywords: Liming; Soil acidity; pH; Base saturation; Calcium; Magnesium